THE CULTURAL OBSTACLE IN THE COMMUNICATION BETWEEN NATIVE SPEAKER AND NON NATIVE SPEAKER IN ENGLISH. - Sogimin Sogimin (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
This research describes the cultural obstacles in the communication oral and written between native speaker and non native speaker in English. The obstacles of cultural is one of main obstacles in the two peoples of communication in the different culural. The research,especially describes the one case of communication between Indonesian people and British people in the social media WhatsApp. The main data of the research is the communication transcript in the social media WhatsApp. Besides of that, the data comes from the interview with the responden. The research is the case study of the Indonesian people and British people. The data analysis uses qualitative and descriptive method. The result of research shows the miscommunication from different cultural in English. This miscommunication not only caused of the skill of language(language competence) but also difference of cultural between of two peoples. Suggested to the English learner that not only learns in the languages aspects but also learns in the cultural aspects, because both of them coud not separate and interplay each others.